Antiulcerogenic Activity of the Hydroalcoholic Extract of Leaves of Croton campestris A. St.-Hill in Rodents - Júnior, Francisco E. B. (Hindawi Publishing Corporation, 2013)
Croton campestris A. St.-Hill., popularly known as “velame do campo,” is a species native to the savannah area of Northeast Brazil, which is used by traditional communities in folk medicine for variety of health problems, especially detoxification, inflammation, and gastritis. The hydroalcoholic extract of C. campestris leaves (HELCC) was assessed for its antiulcerogenic effect in gastric lesion models and effect on intestinal motility in mice, and possible mechanisms of action were examined. HELCC showed significant gastroprotective action in all models of gastric ulcer evaluated; the results suggest that this action probably involves the nitric oxide pathway. HELCC did not show alteration of intestinal motility in mice. It was also found that C. campestris represents a promising natural source with important biological potential, justifying some of its uses in folk medicine.